2015
DOI: 10.1109/tgrs.2014.2326177
|View full text |Cite
|
Sign up to set email alerts
|

Including Antenna Mispointing in a Semi-Analytical Model for Delay/Doppler Altimetry

Abstract: Delay/Doppler altimetry (DDA) aims at reducing the measurement noise and increasing the along-track resolution in comparison with conventional pulse-limited altimetry. In a previous paper, we have proposed a semi-analytical model for DDA, which considers some simplifications as the absence of mispointing antenna. This paper first proposes a new analytical expression for the flat surface impulse response (FSIR), considering antenna mispointing angles, a circular antenna pattern, no vertical speed effect, and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…High quality and dense sampling of geospatial and environmental information is expected not only for coastal management but also for scientific research, e.g., [11]. The increasing demands of coastal applications have motivated excellent efforts in the altimetry community to improve coastal applicability, including proposing new altimetry concepts (Ka-band altimetry [12], delay-Doppler altimetry [13,14], wide-swath altimetry [15], GNSS altimetry [16], constellations of altimeters [17]) and reprocessing conventional altimeter data [18][19][20]. In the last decade, a series of projects were supported by some space agencies and research institutions, aiming to retrieve valid altimeter data as close as possible to the coast.…”
Section: Introductionmentioning
confidence: 99%
“…High quality and dense sampling of geospatial and environmental information is expected not only for coastal management but also for scientific research, e.g., [11]. The increasing demands of coastal applications have motivated excellent efforts in the altimetry community to improve coastal applicability, including proposing new altimetry concepts (Ka-band altimetry [12], delay-Doppler altimetry [13,14], wide-swath altimetry [15], GNSS altimetry [16], constellations of altimeters [17]) and reprocessing conventional altimeter data [18][19][20]. In the last decade, a series of projects were supported by some space agencies and research institutions, aiming to retrieve valid altimeter data as close as possible to the coast.…”
Section: Introductionmentioning
confidence: 99%
“…Similar considerations apply to SAR altimetry, whose echoes have been modeled analytically as functions also of satellite pointing [6]. Moreover, in [7], it has been shown that the along-track mispointing affects the amplitude of the multilooked echoes, so a priori knowledge of the along-track mispointing is needed to correctly retrieve the amplitude of the waveform. Furthermore, for CryoSat, as detailed in [1], precise attitude information is a needed input for the SARIn Level2 processing (particularly the roll) aiming at retrieving the interferometric phase with a sufficient accuracy from the acquired echoes.…”
Section: Introductionmentioning
confidence: 95%
“…In these procedures the main point is the filter tap coefficients are not regular, slightly, they change from one iteration to another, in compliance with the noise corruption left over in the output signal. Here are numerous filtering algorithms existing to fill in the coefficients [7] - [9]. Related to all algorithms the Least Mean Square (LMS) technique is the essential technique.…”
Section: Introductionmentioning
confidence: 99%